Hypertension Treatment Education on Medication Adherence and Control to Health Care Facilities - Fauziah, Ani Nur; Bintari, Siti Harnina; Widowati, Evi; Cahyati, Widya Hary (Universitas Negeri Semarang, 2025)
Hypertension is a leading cause of cardiovascular disease, stroke and premature death. It is a serious public health problem. Reports show that only 54% of adults with hypertension are diagnosed, 42% receive treatment and 21% can control their hypertension. These statistics show how important it is to increase awareness and control of hypertension. This study aims to evaluate the effectiveness of providing hypertension treatment education on medication adherence and control to health care facilities in Indonesia. This study is a cross-sectional analytical study using secondary data from the Indonesia Health Survey (SKI) 2023. The independent variable is hypertension treatment education, the dependent variable is adherence to taking medication and control to health care facilities. Bivariate data analysis used simple linear regression test. The results of providing hypertension education is effective on the regularity of taking anti-hypertensive drugs with statistical test results obtained p-value 0.002, as well as hypertension education is also effective on routine control to health care facilities with p value 0.000. In addition, the factors of age, education, employment and economic status affect the regularity of taking antihypertensive drugs with p value < 0.05. Hypertension treatment education is effective on the regularity of taking medication and control to health care facilities in Indonesia. The characteristics of age, education, employment and economic status affect the regularity of taking antihypertensive drugs.